Low-dose organic arsenic exposure causes chronological changes in colonic mucosa: scanning electron microscopy findings - Zulkiflee, Khodijah; Saharudin, Shahida; Wan Salleh, Wan Muhamad Salahudin; Hamdan, Asmah Hanim; Abdullah, Nor Zamzila; Buyong, Zunariah (2019)
Water supply is a well-known source of arsenic-based pesticide and herbicide contamination. However, studies on the effect of low-dose organic arsenic that mimics arsenic content in drinking water to colonic mucosa are lacking. Thus, this study aimed to determine the effects of low-dose organic arsenic on colonic mucosa by using scanning electron microscopy (SEM). Thirty rats were randomly divided into Arsenic and Control groups. Both were further subdivided into three groups of five rats each according to durations of exposure ie 2, 4 and 6 months. Rats in Arsenic groups were given oral gavage of 42.13 mg/kg organic arsenic daily, while Control rats received distilled water. At the end of studied durations, colon specimens were processed for SEM descriptive analysis. The Control rats’ colonic mucosa showed uniform size of individual glandular units, central crypt orifices and scattered goblet cells. The 2-month Arsenic group showed less homogeneity in the size of glandular units, slit-like crypt orifices and velvety appearance. In the 4-month Arsenic, the glands demonstrated less distinct border with stellate-shaped crypt orifices. After a 6-month exposure, glands were found varied in size and shape with bald and cerebriform appearance. In conclusion, there were chronological changes to colonic mucosal following exposure to low-dose organic arsenic.